2014
DOI: 10.1007/s00296-014-3166-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ischemic stroke in patients with polymyositis and dermatomyositis: a systematic review and meta-analysis

Abstract: Several chronic inflammatory disorders, such as rheumatoid arthritis and systemic lupus erythematosus, have been demonstrated to increase ischemic stroke risk, but the data on polymyositis (PM) and dermatomyositis (DM) remain unclear. We conducted a systematic review and meta-analysis of observational studies that reported odds ratio, relative risk, hazard ratio or standardized incidence ratio comparing ischemic risk in patients with PM/DM versus non-PM/DM participants. Pooled risk ratio and 95 % confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Our estimate for ischemic stroke is similar to what was observed in a recent meta‐analysis (pooled risk ratio 1.61 [95% CI 1.28, 2.02]) and a recent Canadian study (age‐ and sex‐adjusted HRs of 2.46 [95% CI 1.38, 4.41] and 1.86 [95% CI 0.76, 4.32] for patients with PM and patients with DM, respectively). The majority of previous studies estimating the relative risk of stroke associated with IIM have failed to separate hemorrhagic stroke from ischemic stroke , and because these types of stroke have different etiologies, it is important to investigate these outcomes separately.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our estimate for ischemic stroke is similar to what was observed in a recent meta‐analysis (pooled risk ratio 1.61 [95% CI 1.28, 2.02]) and a recent Canadian study (age‐ and sex‐adjusted HRs of 2.46 [95% CI 1.38, 4.41] and 1.86 [95% CI 0.76, 4.32] for patients with PM and patients with DM, respectively). The majority of previous studies estimating the relative risk of stroke associated with IIM have failed to separate hemorrhagic stroke from ischemic stroke , and because these types of stroke have different etiologies, it is important to investigate these outcomes separately.…”
Section: Discussionsupporting
confidence: 89%
“…A few cohort studies have investigated the risk of stroke in patients with PM and those with DM , with all showing an increased risk. A recent meta‐analysis including 3 of these studies demonstrated a pooled relative risk for ischemic stroke of 1.61 in IIM patients compared to non‐IIM populations, but due to the heterogeneity of the included studies, the actual risk of stroke following IIM diagnosis is still uncertain . In addition, few of the studies published thus far have investigated the risk of the 2 main subtypes of stroke (ischemic and hemorrhagic) separately and the stroke risk over time in individuals with IIM.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, several large epidemiological studies have demonstrated an increased incidence of cardiovascular disease among patient with chronic inflammatory disorders, such as rheumatoid arthritis, idiopathic inflammatory myositis, vasculitis, systemic lupus erythematosus and autoimmune liver diseases [1][2][3][4][5][6]. Premature atherosclerosis from chronic inflammation appears to be the cornerstone of these excessive cardiovascular complications [7][8][9].…”
Section: Introductionmentioning
confidence: 98%
“…As previously mentioned, the deleterious role of chronic inflammation in the progression of atherosclerosis is well-established [9][10][11][12][13][14] and an increased risk of coronary artery disease/cerebrovascular disease has been observed in several chronic inflammatory disorders. [4][5][6][7][8] Several studies have also demonstrated an association between elevated CRP and PAD as a study found that elevated CRP was more prevalent in patients with PAD compared with the general population, 29 while another nested case-control study found that among apparently healthy men, baseline levels of CRP could predict future risk of developing symptomatic PAD. 18 Another prospective study also demonstrated that a higher level of CRP was associated with progression of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 An increased incidence of cardiovascular disease has been observed in several chronic inflammatory disorders, such as rheumatoid arthritis, idiopathic inflammatory myositis, systemic sclerosis and systemic lupus erythematosus. [4][5][6][7][8] It is hypothesized that this increased risk is associated with the accelerated atherosclerosis secondary to chronic inflammation as several studies have demonstrated the detrimental effect of inflammatory cytokines, reactive oxidative species and activated inflammation on endothelial function. [9][10][11][12][13][14] Similarly, a recent population-based study also found an increased risk of coronary artery disease (CAD) among patients with GCA.…”
Section: Introductionmentioning
confidence: 99%